Spatial decision support system for assessing lake pollution hazard: Southeastern pampean shallow lakes (Argentina) as a case study - Romanelli, Asunción (2014)
This study gives an account of the implementation of a decision support system as a logical framework for assessing lake pollution hazard. The use of this system is demonstrated with an example from two lake watersheds, each one with different land-use, soil and topographic characteristics and also management regulations for natural resource protection. Lake pollution hazard is assessed as a function of two primary topics: hydrologic and soil conditions. This model shows the state of each evaluated subwatershed with respect to its potential contribution to lake pollution hazard based mainly on easily measurable and commonly used parameters: drainage density, hydraulic gradient, water table depth, soil media, land-cover and topography. Mapped outputs from the logic model allowed the identification of several subwatersheds in each lake system as the main water resource protection areas. La Brava Lake Watershed results reasonably fit the natural conditions of the watershed, identifying those subwatersheds with a moderate to high drainage density, high hydraulic gradient and extensive agricultural activities. Regarding Los Padres Lake Watershed, moderate to high drainage density, a high to a very high hydraulic gradient, shallow water depth, silt-loam soil texture and intensive agricultural and residential lands, contributed to a high lake pollution hazard. Results highlighted differences between both freshwater systems, being Los Padres Lake Watershed a more vulnerable ecosystem, requiring decision maker's intervention based on accurate and up-to-date information.